An Unusual Case of Tracheoesophageal Fistulae. (28th June 2012) - Giquel, Jadelis; Matadial, Christina; Rodriguez Blanco, Yiliam F.; Martinez-Ruiz, Ricardo; Nguyen, Dao; Candiotti, Keith
Abstract : Acquired tracheoesophageal fistulae (TEF) are commonly due to malignancy (M. F. Reed and D. J. Mathisen, 2003). We present the case of a patient with a deceptive history for TEF and report an approach that provides adequate oxygenation, ventilation, surgical exposure, and postoperative analgesia with excellent outcome.